Marketing Mix Analysis of Financing Products BMT Insan Mulia Palembang - Sampurna, Ayat Wijaya; Maftukhatusolikhah, Maftukhatusolikhah; Sumantri, Rinol (Jurnal Iqtisaduna, 2025)
This research was conducted to determine the implementation of the marketing mix at BMT Insan Mulia Palembang. This research uses the 7P marketing mix theory, namely, product, price, place, promotion, people, process, and physical evidence. The research results are that BMT Insan Mulia has implemented all aspects of the 7P marketing strategy well. What is superior is that the product is truly sharia compliant. Then the service uses a deposit pickup system directly connected to the system. As proof of the success of BMT Insan Mulia, many of its members previously were financing members but are now members of the Savings product.